Endoscopic Detorsion Results in Sigmoid Volvulus: Single-Center Experience. (13th May 2020) - Firat, Necattin; Mantoglu, Baris; Ozdemir, Kayhan; Muhtaroglu, Ali; Akin, Emrah; Celebi, Fehmi; Fatih, Altintoprak
Abstract : Endoscopic detorsion is the first-line recommended treatment modality in sigmoid volvulus patients who have no peritoneal irritation signs on admission. In this paper, we present the results of endoscopic detorsion procedures applied at the time of presentation with the diagnosis of sigmoid volvulus and review the current literature about this topic.